A new genus of an Oriental Rhyparochromini (Heteroptera: Rhyparochromidae) to place Caridops albomarginatus (Scott, 1874) and the use of SDM to test an extra-Palaearctic record - Dellapé, Pablo Matías (2017)
The new genus Scudderocoris (Heteroptera: Rhyparochromidae: Rhyparochromini) is established to accommodate Caridops albomarginatus, a species known from China, Japan, and South Korea: Scudderocoris albomarginatus (Scott, 1874) comb. nov. The species is redescribed and photographs of the adult male and its genitalia are provided. The finding of a male specimen labeled from South America is intriguing. To evaluate if this species could find suitable climatic conditions in the Neotropics, we performed a Species Distributional Model (SDM), based on native distribution records, and compared the bioclimatic variables between the native range and the area where the specimen was supposedly collected. Our conclusion that the specimen was mislabeled, shows that SDM can be a useful tool in detecting collection label biases.